Rapid procedure for the extraction of DNA from fungal spores and mycelia. - J. J. Weiland (Fungal Genetics Reports, 1997)
A method is described for the reliable preparation of DNA from fungal spores and mycelia and from plant tissues. A number of fungal and plant species were used in the study to indicate the generality of the method. The DNA prepared by this protocol was digested by restriction endonucleases and served as template using standard polymerase chain reaction conditions.